The Direct Testing Effect Is Pervasive in Action Memory: Analyses of Recall Accuracy and Recall Speed - Kubik, Veit; Jönsson, Fredrik U.; Knopf, Monika; Mack, Wolfgang (Frontiers in Psychology, 2018)
Successful retrieval from memory is a desirably difficult learning event that reduces the recall decrement of studied materials over longer delays more than restudying does. The present study was the first to test this direct testing effect for performed and read action events (e.g., “light a candle”) in terms of both recall accuracy and recall speed. To this end, subjects initially encoded action phrases by either enacting them or reading them aloud (i.e., encoding type). After this initial study phase, they received two practice phases, in which the same number of action phrases were restudied or retrieval-practiced (Exp. 1 & 2), or not further processed (Exp. 3; i.e., practice type). This learning session was ensued by a final cued-recall test both after a short delay (2 minutes) and after a long delay (1 week: Exp. 1 & 2; 2 weeks: Exp. 3). To test the generality of the results, subjects retrieval-practiced with either noun-cued recall of verbs (Exp. 1 & 3) or verb-cued recall of nouns (Exp. 2) during the intermediate and final tests (i.e., test type). We demonstrated direct benefits of testing on both recall accuracy and recall speed. Repeated retrieval practice, relative to repeated restudy and study-only practice, reduced the recall decrement over the long delay, and enhanced phrases’ recall speed already after 2 minutes, and this independently of type of encoding and recall test. However, a benefit of testing on long-term retention only emerged (Exp. 3), when prolonging the recall delay from one to two weeks, and using different sets of phrases for the immediate and delayed final tests. Thus, the direct testing benefit appears to be highly generalizable even with more complex, action-oriented stimulus materials, and encoding manipulations. We discuss these results in terms of the distribution-based bifurcation model.